Plasmonics: Resistless Nanoimprinting in Metal for Plasmonic Nanostructures (Small 22/2013). Issue 22 (25th November 2013) - Varghese, Leo T.; Fan, Li; Xuan, Yi; Tansarawiput, Chookiat; Kim, Sangsik; Qi, Minghao
<x xml:space="preserve">Abstract</x> A simple metal nanopatterning process named resistless nanoimprinting in metal (RNIM) is proposed and demonstrated by Y. Xuan, M. Qi, and co‐workers on page 3778. This allows metal films to be directly imprinted at low temperatures and low pressures without the need for resists or any intermediate layers. High‐resolution patterns with smooth and vertical side‐walls are generated on metals such as Ag and Au. The RNIM process can be used to pattern metals for applications in plasmonics, metamaterials, biological sensing, and microfluidics. A vivid image of a butterfly seen through a perforated metal film is illustrated in the cover image as a demonstration of extraordinary optical transmission. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>